Pengembangan Aplikasi Android Matematika Untuk Anak Usia Dini - Azro’I, Imam; Putri, Farah Kamelia Ali; Nisfah, Nia Lailin; Anisah, Al Khoridatul; Fitriyanti, Desy (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
Abstract Teachers at Early Childhood Education institutions stated that mathematics lessons for Early Childhood (AUD) only included the introduction of numbers, geometry and measurement. Whereas according to the (National Council of Mathematics Teachers), mathematics for AUD includes 5 standard mathematical processes: problem solving, reasoning and proof, communication of mathematical ideas, mathematical representations, and mathematical connections, and includes 5 content standards which include Numbers and their operations, algebra, geometry , measurement, data analysis and probability. The results of the PISA score show that mathematics needs to be taught from an early age (since in Early Childhood Education institutions) so that students are familiar with mathematical calculations. The purpose of this research is to make mathematics learning media that can be used by early childhood easily and is also accompanied by quizzes. The method in this study is the Research and Development (R&D) method. The research that will be carried out by researchers is the development of information systems, because of that their R&D research uses a special approach to designing information systems. The approach used in the design of information systems will be carried out using the SDLC (System Development Life Cycle) method. Keywords: Early Chilhood Math; Android; SDLC; Mobile Application Abstrak Guru lembaga Pendidikan Anak Usia Dini menyatakan bahwa untuk pelajaran matematika bagi Anak Usia Dini (AUD) hanya meliputi pengenalan angka, geometri dan pengukuran. Padahal menurut (The National Council of Teachers of Mathematics), matematika untuk AUD meliputi ada 5 standar proses matematika: pemecahan masalah, penalaran dan pembuktian, komunikasi gagasan matematika, representasi matematika, dan koneksi matematika, dan meliputi 5 standar isi yang meliputi Angka dan operasionalnya, aljabar, geometri, pengukuran, analisis data dan probabilitas. Hasil skor PISA mengindikasikan bahwa matematika perlu diajarkan sejak dini (sejak di lembaga Pendidikan Anak Usia Dini) agar siswa terbiasa dengan perhitungan matematika. Tujuan Penelitian ini adalah untuk membuat media pembelajaran matematika yang dapat digunakan oleh usia anak usia dini secara mudah dan juga disertai dengan kuis. Metode dalam penelitian ini adalah metode Research and Development (R&D). Penelitian ini menggunakan metode R&D dengan pengembangan sistem informasi, dan menggunakan pendekatan khusus untuk perancangan sistem informasi. Pendekatan yang digunakan dalam perancangan sistem informasi yang dilakukan menggunakan metode SDLC (Sistem Development Life Cycle). Kata kunci: Matematika Anak Usia Dini; Android; SDLC; Aplikasi Seluler